2008
DOI: 10.1136/thx.2006.075077
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of viral community-acquired pneumonia in adults

Abstract: Background: In adults, viral causes of communityacquired pneumonia (CAP) are poorly characterised. The aims of this study were to characterise the viral aetiology of CAP in adults by using an extensive array of viral diagnostic tests and to compare the characteristics of viral pneumonia with those of pneumococcal pneumonia. Methods: Adults admitted to Christchurch Hospital over a 1-year period with CAP were included in the study. Microbiological testing methods included blood and sputum cultures, urinary antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
359
11
29

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(443 citation statements)
references
References 39 publications
44
359
11
29
Order By: Relevance
“…They were observational cohort studies except for one case-control study [34]. They were published between 2005 and 2015 and carried out in Europe (n=14) [1, 3, 5, 18-24, 26, 28, 33, 35], Asia (n=9) [2, 6, 10, 29-32, 34, 36], North America (n=4) [11,12,25,27], Oceania (n=3) [7,8,17] and South America (n=1) [9]. These studies enrolled a predominantly adult population although two of them used a cut-off of age >14 years for inclusion [3,31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They were observational cohort studies except for one case-control study [34]. They were published between 2005 and 2015 and carried out in Europe (n=14) [1, 3, 5, 18-24, 26, 28, 33, 35], Asia (n=9) [2, 6, 10, 29-32, 34, 36], North America (n=4) [11,12,25,27], Oceania (n=3) [7,8,17] and South America (n=1) [9]. These studies enrolled a predominantly adult population although two of them used a cut-off of age >14 years for inclusion [3,31].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly identified viruses were influenza in 18 studies [3, 6, 7, 10, 11, 17-19, 21, 23, 26, 27, 29, 31, 32, 34-36], rhinovirus in eight studies [1,5,8,12,22,24,25,28], respiratory syncytial virus in three studies [2,9,33] and coronavirus in two studies [20,30]. Meta-analyses revealed that the proportion of infection by influenza (31 studies) was 8% (95% CI 6.3-9.6%; I 2 =91.9%), by rhinovirus (25 studies) was 5.7% (95% CI 4.3-7.1%; I 2 =90.3%), by respiratory syncytial virus (29 studies) was 2.2% (95% CI 1.6-2.8%; I 2 =80%) and by coronavirus (18 studies) was 3.3% (95% CI 2.3-4.2%; I 2 =80.2%).…”
Section: Individual Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, myalgia was associated with pneumonia caused by a respiratory virus and with influenza pneumonia. 32 Perhaps our study population of CAP patients initially evaluated by primary care clinicians in ambulatory settings includes a significant proportion of patients with primary viral pneumonia. Such individuals would be expected to have a slow or nonresponsive course following onset of antibiotic treatment (i.e.…”
Section: Discussionmentioning
confidence: 99%